Исследование иммунного статуса пациентов с разной формой атопического дерматита - Высоцкая, Е. В.; Трубицын, А. А. (ХНУРЭ, 2008)
The given work is devoted to the questions of patient’s immune status research with a different form of atopic dermatitis (AD). For the adequate evaluation the state of patient and determinations the risk of disease development is offered by authors to use the complex index S. Verification the fitness of parameters offered criterion for the state of patients with different forms AD, conducted on experimentahnaterial, showed its enough high informing.
Keywords: атопический дерматит; исследование иммунного статуса